Toxicidade de extratos de Andira paniculata (Fabaceae) em Helicoverpa armigera (Lepidoptera: Noctuidae) - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
The Helicoverpa armigera caterpillar has been one of the most importante pest in soybean crop in Brazil. The objective of this study was to evaluate the effect of organic extracts of Andira paniculata in the biology, feeding and attractiveness of H. armigera in soybean plants. The experiments were performed at the Entomology Laboratory of the Goiano Federal Institute (IF Goiano), Campus Urutaí, Goias State, Brazil. The fractions of hexane, dichloromethane, ethyl acetate and hydroalcoholic in the concentrations of 0.01, 0.1, 0.5 and 1% were evaluated. For the biological parameters were evaluated the period and viability of larval stage, weight of caterpillars at ten days, period, viability and pupal weight with 24 hours, total cycle, LC50 and deterrence. The atractiveness and no preference for feeding, the number of caterpillars and the dry matter consumed in each fraction of the extracts were evaluated. The extract of A. paniculata in hexane (0.01%) caused the death of up to 85% of H. armigera. The extract of A. paniculata did not affect the larval period, weight, period and pupal mortality and the consumption of H. armigera. The hydroalcoholic extracts obtained the better results for deterrence. The A. paniculata extract in dichloromethane fraction had the lowest LC50. The extracts of A. paniculata in the hexane fractions (0.1%), ethyl acetate (0.01 and 0.5%) and hydroalcoholic (0.01 and 0.5%) were fagodeterrente to H. armigera. Thus, A. paniculata extract in hexane fraction is the most promising for use in the control of H. armigera in soybean. Keywords: Insecta, Botanical Insecticid
Keywords: Insecta; Inseticida botânico; Deterrência; Controle de pragas; Glycine max; Insecta; Botanical Insecticide; Deterrence; Control of pest; Glycine max.; CIENCIAS AGRARIAS